Pemanfaatan Media Pembelajaran konsep perkalian dan pembagian di MI - Irwaniyati, Ika (Pendidikan Islam Pascasarjana IAIN Jember, 2018)
This study aims to: (1) describe the preparation of media utilization in learning the concept of multiplication and distribution in Madrasah Ibtidaiyah Miftahul Ulum Serut 01, (2) to describe media utilization activity in multiplication concept learning and distribution in Madrasah Ibtidaiyah Miftahul Ulum Serut 01, and (3 ) Describes the follow-up of media utilization in multiplication concept learning and distribution in Madrasah Ibtidaiyah Miftahul Ulum Serut 01. This research uses qualitative approach, with qualitative descriptive method. Type of research used case study. The location of research is Madrasah Ibtidaiyah Miftahul Ulum Serut 01 Serutan Panti Jember. Research subject is determined by purposive technique. Data collection techniques using observation, interviews, and documentation. Data analysis using interactive techniques Miles and Huberman model includes data collection, data reduction, display data, and conclusion: drawing / verification. Data validity technique used in this research is credibility test through triangulation and member check. Triangulation used includes triangulation of data sources and data collection techniques. The results of the research are as follows: (1) Preparation of media utilization in multiplication concept learning and distribution in Madrasah Ibtidaiyah Miftahul Ulum Serut 01 include: (a) media selection based on learning objectives and materials, access to media, mastery of use, and conformity with the level of development of participants (b) the media is strived to come from everyday learners, so that learners feel that the material learned closely and can be applied in daily life, (c) the preparation of clear media demonstration instructions by teachers to direct the focus of learners on the learning process that took place. (2) Media utilization activities in multiplication concept learning and distribution in Madrasah Ibtidaiyah Miftahul Ulum Serut 01, include: (a) media layout and student seating arranged to enable access of all learners to media and interaction among learners and participation active learners, (b) media utilized involving the demonstration and active participation of learners through the selection of appropriate strategies and methods. (3) The follow-up of media utilization in learning the concept of multiplication and distribution in Madrasah Ibtidaiyah Miftahul Ulum Serut 01, covering: (a) Discussion both group and classical to draw conclusion, so the concept formed is the result of discovery (learners) the learning sequences experienced. (b) evaluation of media support to the learning materials integrated in the learning series through the evaluation instrument of learning achievement objectives.